2020
DOI: 10.3389/fmicb.2020.01159
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Release Inhibitors Generated by Fermentation of Artemisia princeps Pampanini Herb Extract With Lactobacillus plantarum SN13T

Abstract: Some glycosides, which are detected in water extracts from medicinal plants, have been reported to be degraded into their aglycones by incubating with some microorganisms producing β-glucosidase. We have shown that a plant-derived Lactobacillus plantarum SN13T harbors 11 open reading frames (ORFs) encoding the β-glucosidase enzyme and can grow vigorously in several herbal water extracts. In this study, we observed that the water extract from Artemisia princeps Pampanini (AP) fermented with the SN13T strain str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…Our study shows that both IL-8 and IL-1β are reduced in infected D6234 primary oral epithelial cells in the presence of Auraguard, suggesting that the plaque-derived bacterial pathogens will have a lesser impact on the host oral epithelium. Plant extracts are accountable for similar results on IL-8 reduction, and this pattern of reduced IL-8 secretion was demonstrated with plant extracts on HuH-7 cells [49] and Caco-2 cells [33]. It is also possible that the reduced IL-8 secretion is caused by the reduced IL-1β secretion, as it has been reported that IL-1β mediates IL-8 secretion in some instances [33].…”
Section: Discussionsupporting
confidence: 72%
“…Our study shows that both IL-8 and IL-1β are reduced in infected D6234 primary oral epithelial cells in the presence of Auraguard, suggesting that the plaque-derived bacterial pathogens will have a lesser impact on the host oral epithelium. Plant extracts are accountable for similar results on IL-8 reduction, and this pattern of reduced IL-8 secretion was demonstrated with plant extracts on HuH-7 cells [49] and Caco-2 cells [33]. It is also possible that the reduced IL-8 secretion is caused by the reduced IL-1β secretion, as it has been reported that IL-1β mediates IL-8 secretion in some instances [33].…”
Section: Discussionsupporting
confidence: 72%
“…Previously, extracts from medicinal plants like Artemisia princeps Pampanini and Paeonia lactiflora Pall had been fermented with plant-derived L. plantarum SN13T and L. brevis 174A, respectively, which generated additional bioactive compounds in the plant extracts (Okamoto et al, 2020;Shakya et al, 2021). In this study, we further attempted to ferment P. lactiflora Pall (Paeonia Radix Alba) and Carthamus tinctorius extracts with PLA-producing strains MSC-C2 and K40.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has isolated over 1,200 strains of plant-derived LAB from fruits, vegetables, flowers, and medicinal plants and evaluated their health benefits, such as immune modulation, liver function improvement, and reduction of obesity (Jin et al, 2010;Zhao et al, 2012;Noda et al, 2018). Further, when cultivated in plant extracts, some of the plant-derived LAB-produced substances that have shown therapeutic potential (Okamoto et al, 2020;Shakya et al, 2021). Therefore, we also determined the PLA production by L. plantarum MSC-C2 isolated from sugarcane and P. pentosaceus K40 isolated from banana in extracts from the medicinal plants Paeonia lactiflora Pall and Carthamus tinctorius and studied the potential of PLA-containing LAB-medicinal plant extracts against the biofilm and virulence genes of periodontopathogen A. actinomycetemcomitans.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LAB-fermented plants have been applied to treat diabetes and liver diseases in rats [21], reduce stress [22], and inhibit the proliferation of cancer cell lines better than non-fermented plant extracts [23]. Artemisia princeps Pamp., fermented by Lactobacillus plantarum SN13T, showed therapeutic potential by reducing the release of interleukin-8 in a human hepatoma cell line [24]. In these applications, predominantly single LAB strains were applied.…”
Section: Introductionmentioning
confidence: 99%